Optimization of injection molding parameters for bending and tensile strength of ABS and ABS/carbon fiber composites using Taguchi–Grey correlation analysis - Hieu Giang Le; Thanh Trung Do; Tran Minh The Uyen; Bui Chan Thanh; Pham Son Minh (PLoS ONE, 2026)
This study investigates the effects of injection molding parameters on the flexural and tensile strengths of neat acrylonitrile–butadiene–styrene (ABS) and woven carbon fiber fabric–reinforced ABS composites (ABS/CF) fabricated by a two-step insert injection molding process. A Taguchi L25 orthogonal experimental design was employed with five processing parameters: filling pressure (104–118 MPa), packing pressure (96–100 MPa), filling time (1–3 s), packing time (0.5–2.5 s), and melt temperature (228–232 °C). The results show that flexural strength increased from 5.86–6.49 MPa (ABS) to 5.76–6.93 MPa (ABS/CF), while tensile strength increased from 33.35–35.17 MPa to 38.20–41.27 MPa, corresponding to improvements of approximately 7% and 17–18%, respectively. ANOVA results indicate that filling pressure is the most significant factor, with p-values of 0.012 and 0.039 for flexural performance and a maximum contribution of 47.08% for tensile strength. The optimal parameter combination identified by Taguchi–Grey analysis yields Grey relational grades of 0.725 and 0.728 for flexural and tensile strength, respectively. Confirmation experiments show good agreement with predicted values, with deviations of 1.59% (flexural) and 2.98% (tensile). Overall, this study provides a comprehensive understanding of the process–structure–property relationships in injection-molded ABS/CF composites and demonstrates that the Taguchi–Grey approach is an effective method for simultaneous optimization of multiple mechanical properties. The findings offer practical guidelines for improving the mechanical performance of fiber-reinforced thermoplastic composites in thin-walled and structural applications.